Getting On With Pain - McCarthy, Judy (Murmurations: Journal of Transformative Systemic Practice, 2023)
This paper provided the welcome opportunity to write about how I have come to understand and relate to chronic pain. My systemic psychotherapy training and interest in Narrative Practice has strongly influenced my conceptualisation of pain. I have found this useful in my experience of living with chronic pain. I hope the reader is invited to reflect on the many dimensions of pain and illness and the multitude of possibilities for understanding and relating to it. I experience pain as a very significant aspect of my life and my relationships including therapeutic relationships. For this reason, I believe it is important to talk about the therapist’s illness and health conditions in the same way that other aspects of human experiences are talked about.